In vitro antagonism caused by some species of fungi on Rigidoporus lignosus - Jayasuriya K E; Deacon J W; Fernando T H P S (Journal of the Rubber Research Institute of Sri Lanka, 1996)
Fungi potentially antagonistic to Rigidoporus lignosus were isolated from a) by placing soil samples on agar plates previously colonized by R. lignosus, or on Trichoderma selective agar and b) from basidiomycete fruit bodies in rubber plantations. Modes of action of potential antagonists against R. lignosus were evaluated by in vitro methods viz: production of volatile or non-volatile inhibitory compounds and ability to overgrow colonies of R. lignosus on agar. Some Trichoderma spp. were strongly antagonistic to R. lignosus in most of the tests. T. longibrachiatum (isolate DZE10) completely inhibited R. lignosus on agar by producing voolatile inhibitory metabolities. Trametes sp. (isolates ISO16 & KIR8) antagonized R. lignosus on dual membered plates.
Keywords: Antagonism; Antagonism; Biocontrol; Hevea brasiliensis; Mycelial cords; Rigidoporus lignosus